Red evening : the story in multiple translations - Dāsa, Kiśorīcaraṇa (Multiple translations series, 2008)
Red evening / translated by the author -- A scarlet evening / translated by K.K. Mohapatra, Leelawati Mohapatra and Paul St-Pierre -- A crimson evening / translated by Prajna Paramita -- A red evening / translated by Chandramoni Narayanswamy